Systematic analysis reveals novel insight into the molecular determinants of function, diversity and evolution of sweet taste receptors T1R2/T1R3 in primates - Wang, Congrui; Liu, Yi; Cui, Meng; Liu, Bo (Frontiers in Molecular Biosciences, 2023)
Sweet taste is a primary sensation for the preference and adaption of primates to diet, which is crucial for their survival and fitness. It is clear now that the sweet perception is mediated by a G protein-coupled receptor (GPCR)-sweet taste receptor T1R2/T1R3, and many behavioral or physiological experiments have described the diverse sweet taste sensitivities in primates. However, the structure-function relationship of T1R2s/T1R3s in primates, especially the molecular basis for their species-dependent sweet taste, has not be well understood until now. In this study, we performed a comprehensive sequence, structural and functional analysis of sweet taste receptors in primates to elucidate the molecular determinants mediating their species-dependent sweet taste recognition. Our results reveal distinct taxonomic distribution and significant characteristics (interaction, coevolution and epistasis) of specific key function-related residues, which could partly account for the previously reported behavioral results of taste perception in primates. Moreover, the prosimians Lemuriformes species, which were reported to have no sensitivity to aspartame, could be proposed to be aspartame tasters based on the present analysis. Collectively, our study provides new insights and promotes a better understanding for the diversity, function and evolution of sweet taste receptors in primates.